Reducing the unemployment rate through the development of ethnotourism in Kazakhstan - Lambekova, А.N.; Galinova, A.T.; Rakhimbaeva, R.M.; Alisheva, D.E. (BUKETOV BUSINESS REVIEW, 2023)
Object: To familiarize the local population with traditions and cultures through the development of ethnic tourism in Kazakhstan. Reduction of unemployment due to the development of ethnotourism. Methods: In the course of the study, methods of mathematical, economic and system analysis of the unemployment rate in the Republic of Kazakhstan were used. In addition, the target audience was determined, a survey of the population was conducted, it was determined what types of work should be provided to the population through the development of ethnotourism, as well as the needs and desires were determined. Findings: As a result of the study, during the development of agrotourism, a decrease in the unemployment rate was achieved, ensuring employment of the population. The infrastructure, potential, prospects of development, convenience of development of ethnoauls in the Republic of Kazakhstan are investigated. Discussions: Currently, the results of the study are a source of very topical issues of the development of rural ethnotourism, employment of the local population. Thanks to agrotourism, the globalization of ethnic tourism, the country's economy is becoming one of the main tourist destinations that are just beginning to develop and grow. In the course of the study of ethnotourism as a new direction of tourism, providing employment of the population in settlements, the factors influencing the reduction of the unemployment rate are determined. Thanks to the popularization of the traditions and culture of the people, crafts and history, the attention of foreign citizens and the local population was attracted. This article discusses new prospects for the development of ethnotourism in our country.